2021
DOI: 10.1038/s41366-021-00982-4
|View full text |Cite
|
Sign up to set email alerts
|

Internalised weight stigma as a mediator of the relationship between experienced/perceived weight stigma and biopsychosocial outcomes: a systematic review

Abstract: Objective To systematically review studies that have assessed the mediating role of internalised weight stigma on the relationship between experienced/perceived weight stigma and any biopsychosocial outcomes. Methods PsycINFO, PsycExtra, Web of Science, CINAHL, Medline and Embase were systematically searched. Identified studies were double screened (HB and XPG). Results Seventeen studies (across 16 articles) met our inclusion criteria ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 69 publications
5
46
0
1
Order By: Relevance
“…Internalized weight bias (IWB) encompasses self‐blame and self‐devaluation that results from endorsing negative social messages around weight and applying them to the self 3 . IWB is believed to explain the relationship between acutely experienced or indirectly perceived weight stigma and maladaptive eating behaviors 41–43 as well as body shame and dissatisfaction, exercise and healthcare behaviors, bodily pain and parental weight talk 44 . Stigma may lead to efforts of escaping discrimination through weight‐loss attempts, 45 and thus, some have argued that it may have a positive role in motivating individuals to engage in health behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internalized weight bias (IWB) encompasses self‐blame and self‐devaluation that results from endorsing negative social messages around weight and applying them to the self 3 . IWB is believed to explain the relationship between acutely experienced or indirectly perceived weight stigma and maladaptive eating behaviors 41–43 as well as body shame and dissatisfaction, exercise and healthcare behaviors, bodily pain and parental weight talk 44 . Stigma may lead to efforts of escaping discrimination through weight‐loss attempts, 45 and thus, some have argued that it may have a positive role in motivating individuals to engage in health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…3 IWB is believed to explain the relationship between acutely experienced or indirectly perceived weight stigma and maladaptive eating behaviors [41][42][43] as well as body shame and dissatisfaction, exercise and healthcare behaviors, bodily pain and parental weight talk. 44 Stigma may lead to efforts of escaping discrimination through weight-loss attempts, 45 and thus, some have argued that it may have a positive role in motivating individuals to engage in health behaviors. However, stigmatization creates a dual and countervailing effect of increasing motivation to engage in unhealthy weight-control behaviors, while simultaneously decreasing the perceived capacity to control weight, 46 and is consistently linked to adverse health behaviors and decreased long-term health.…”
mentioning
confidence: 99%
“…Longitudinal studies have suggested that obesity may be both a cause and a consequence of mental distress, creating a vicious circle [ 15 , 16 ]. On the one hand, obesity-related stigmatization may result in high mental distress [ 20 , 21 , 22 ]; on the other hand, inappropriate eating behaviors (e.g., emotional eating) may lead to obesity in individuals with poor mental health and maladaptive coping strategies [ 23 ]. Moreover, the effect of antipsychotic medication for the treatment of psychiatric disorders (e.g., schizophrenia [ 24 ]) is a risk factor for severe weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…However, weight-related self-stigma is distinct from the two other types of weight stigma, PWS and experienced stigma. Furthermore, perceived and experienced weight stigma could be categorized as ‘public stigma,’ a broad term for stigma [ 7 ]. Following the findings from a systematic review and meta-analysis [ 5 , 7 ], we used PWS to indicate both perceived and experienced weight stigma in the present study.…”
Section: Introductionmentioning
confidence: 99%